Biomechanical insights on Tennis Canada`s skill fundamental phases: Ecological dynamics, force generation and reading gameplay - Hopper, T.; Rhoades, J. (Coaching and Sport Science Review, 2023)
Using an ecological dynamics perspective and informed by a game-based approach to coaching tennis, this paper applies a biomechanical analysis to Tennis Canada`s five fundamental skill phases, namely recovery, impact point, set-up, hitting zone and grip, along with tactical concepts of time, space, force, and risk. The intent of this paper is to locate, within the player reading gameplay, the biomechanical principles for force generation in tennis strokes that inform Tennis Canada`s five fundamental skill phases. We suggest that these fundamentals can be effectively employed during gameplay so that force can be considered a part of tactical awareness. From a game-based approach we consider gameplay as referring to a player`s ability to read the emerging patterns of play, as critical to successful application of biomechanical principles to stroke mechanics. We propose that perception-action coupling ideas from ecological psychology, guided by the 4R model of read, respond, react, and recover for the stroke movement cycle, promotes both novice and advance tennis players ability to play tennis. The goal of this paper is therefore to help the tennis teaching professional combine ideas from sports pedagogy, biomechanics, and motor learning into the coaching of tennis players, so that their tennis players can experience the flow of forces from a well-played point.